Tarefas de tradução, planejamento colaborativo para repetição e desempenho oral em L2 - Alves, Maria Lueuda Pereira (2024)
Between the 17th and 19th centuries, language teaching was dominated by the Grammar and Translation approach. Over the years, the Direct Method emerged as an alternative, emphasizing full immersion in the target language and completely excluding translation from the classroom. Moreover, the Audiolingual and the Communicative Method also arose, avoiding translation, prioritizing the repetition of linguistic patterns, and communication in real situations. Nowadays, the Post-Method Approach recognizes the importance of adapting teaching methods according to students' needs and considers translation as a valuable tool (ATKINSON, 1993; LUCINDO, 2006; TESSARO, 2012; CORRÊA, 2014; BHATTI, 2018; GUTIÉRREZ, 2019). Within this context, task-based language teaching has been considered by authors such as Ellis (2003) and Skehan (1996) as an effective pedagogical approach, using real and meaningful tasks as the primary means of language learning. Research on planning and repetition shows that integrating prior knowledge with a subsequent encounter with the same task leads to changes in students' performance (BYGATE; SAMUDA, 2005; ASHCRAFT, 1994). This study focuses on the field of planning for task repetition (D’ELY, 2006) and investigates the effects of collaborative planning for the repetition of an oral translation task in L2. More specifically, it aims to understand if collaborative peer planning for repetition leads to statistically significant differences in terms of accuracy and how students perceive this type of planning. This study involved 12 students from the English/ Literature degree course at the Federal University of Ceará. They were subjected to data collection through a biodata questionnaire, an oral translation task of an advertisement, and two post-task questionnaires. Oral performance was measured through accuracy and calculated in two ways: number of errors per 100 words and percentage of error-free clauses. Despite variations in the descriptive data suggesting a possible gain, statistical analyses showed that there were no significant differences in either measure. The qualitative analysis of data obtained from the questionnaires revealed a highly positive perception among students regarding the use of collaborative planning for repetition.